The evolutionary stability of attenuators that mask information about animals that social partners can exploit. (23rd March 2018) - Hackett, Sean; Ruxton, Graeme D.
Abstract: Signals and cues are fundamental to social interactions. A well‐established concept in the study of animal communication is an amplifier, defined as a trait that does not add extra information to that already present in the original cue or signal, but rather enhances the fidelity with which variation in the original cue or signal is correctly perceived. Attenuators as the logical compliment of amplifiers: attenuators act to reduce the fidelity with which variation in a signal or cue can be reliably evaluated by the perceivers. Where amplifiers reduce the effect of noise on the perception of variation, attenuators add noise. Attenuators have been subject to much less consideration than amplifiers; however, they will be the focus of our theoretical study. We utilize an extension of a well‐established model incorporated signal or cue inaccuracy and costly investments by emitter and perceiver in sending and attending to the signal or cue. We present broad conditions involving some conflict of interest between emitter and perceiver where it may be advantageous for emitters to invest in costly attenuators to mask cues from potential perceivers, and a subset of these conditions where the perceiver may be willing to invest in costly anti‐attenuators to mitigate the loss of information to them. We demonstrate that attenuators can be evolutionary stable even if they are costly, even if they are sometimes disadvantageous and even if a perceiver can mount counter‐measures to them. As such, we feel that attenuators of cues may be deserving of much more research attention.